ACHIEVING HARMONY THROUGH PROGRESSIVE ISLAMIC DIMENSIONS IN THE THINKING OF ABDULLAH SAEED - Rusdiana Navlia Khulaisie; Azhar A. Hafizh; Abdul Wafi; Sofia Sofia (Islam Realitas: Journal of Islamic and Social Studies, 2019)
This article aims at describing the Progressive Islam; an Islam that offers a contextualization of the interpretation of Islam that is open, friendly, fresh, and responsive to every humanitarian issue according to Abdullah Saeed's thinking. Progressive Islam is a trend as a continuation of the Liberal Islamic Movement which emerged since approximately one hundred and fifty years ago. This trend emerged as a form of the expression of their dissatisfaction towards the Liberal Islamic Movement which emphasises more on internal criticism of the views and behaviours of Muslims that are deemed not or less in accordance with humanist values. This research was included in the literature research (library research method) which examines the researches and concepts of Progressive Islam in the perspective of Abdullah Saeed's thinking. Therefore, the final results of this study present that Abdullah Saeed offers a concept of understanding Islam that can answer the needs of the Contemporary Muslim communities so that it can be applied as lasting doctrine throughout the space of time and placeArtikel ini mendeskripsikan tentang Islam Progresif, bahwa Islam Progresif adalah Islam yang menawarkan sebuah kontekstualisasi penafsiran Islam yang terbuka, ramah, segar, dan responsif terhadap setiap  persoalan kemanusian menurut pemikiran Abdullah Saeed. Islam Progresif merupakan sebuah tren sebagai kelanjutan dari gerakan Islam liberal yang muncul sejak kurang lebih seratus lima puluh tahun yang lalu. Tren ini muncul sebagai bentuk ungkapan ketidakpuasan mereka terhadap gerakan Islam liberal yang lebih menekankan pada kritik internal terhadap pandangan dan perilaku umat Islam yang dianggap tidak atau kurang sesuai dengan nilai humanis. Penelitian ini termasuk dalam penelitian kepustakaan (library research) yaitu menelaah penelitian dan konsep Islam Progresif dalam perspektif pemikiran Abdullah Saeed. Hasil Akhir dari penelitian ini menunjukkan bahwa Abdullah Saeed menawarkan sebuah konsep pemahaman Islam yang dapat menjawab kebutuhan masyarakat muslim kontemporer sehingga dapat diaplikasikan sebagai ajaran yang abadi di sepanjang kurun waktu dan tempat